Guest Editors’ Introduction Individual and Organizational Reintegration after Ethical or Legal Transgressions: Challenges and Opportunities - Goodstein, Jerry (Business ethics quarterly, 2014)
In this article we set the context for this special issue focusing on individual and organizational reintegration in the aftermath of transgressions that violate ethical and legal boundaries. Following a brief introduction to the topic we provide an overview of each of the four articles selected for this special issue. We then present a number of potentially fruitful empirical, theoretical, and normative directions management and ethics scholars might pursue in order to further advance this evolving literature.